Effect of hypovitaminosis D and its related factors in pregnant women and their newborns - Sandhu, Amrita; Nautiyal, Ruchira; Mehrotra, Vinit; Wasim, Sanober (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal and fetal vitamin D deficiency has nowadays emerged as a frequent morbidity. Adequate vitamin D concentrations during pregnancy are necessary to maintain neonatal calcium homeostasis, bone maturation and mineralization. Objectives of this study were to evaluate serum vitamin D concentration in mothers and its correlation with neonatal cord blood vitamin D at the time of delivery and to study the impact of hypovitaminosis on neonatal anthropometry. Effect of related factors like calcium (Ca), alkaline phosphatase (ALP) and parathyroid hormone (PTH) on maternal vitamin D levels were to be evaluated. Methods: Cross sectional study was done on a total of 220 healthy uncomplicated antenatal females with singleton pregnancy attending labor room at the time of delivery. Maternal and neonatal cord blood samples were drawn in the delivery room and analyzed. Neonatal anthropometry was recorded. Correlations among various maternal and neonatal factors were studied. Results: Widespread vitamin D deficiency was observed in expectant subjects and neonates with 70.91% having deficient levels which were also reflected in newborns (71.82%). Maternal ALP (r= -0.5503, p=0.000) bears a weak negative correlation (p<0.05), maternal serum Ca positive correlation (r = 0.7486, p=0.000) and plasma PTH levels a negative correlation (r = -2.084, p=0.000) with hypovitaminosis. No significant correlation was observed between neonatal anthropometry and vitamin D levels. Conclusions: High prevalence of hypovitaminosis was observed among pregnant women and their neonates in this study. A positive linear relationship was seen between maternal and cord blood vitamin D (r 0.974, p 0.0001).